ADAPTING ARCHITECTURAL AND CONSTRUCTION COMPANIES TO EUROPEAN NORMS AND STANDARDS: RECOMMENDATIONS AND A STEP-BY-STEP TRANSITION ALGORITHM - Kubanov, Ruslan A.; Makatora, Dmytro А.; Mykhalko, Anastasiia О. (Journal of Strategic Economic Research, 2025)
The article is devoted to the theoretical and applied foundations of adapting architectural and construction companies to European norms and standards in the context of Ukraine’s strategic integration into the single economic, technical, and institutional space of the EU. The relevance of the study has been substantiated in connection with increasing regulatory pressure, requirements for operational transparency, digital transformation, and corporate social responsibility. Considering global challenges such as climate change, resource vulnerability, and sustainable development imperatives, the article emphasizes the need for a systematic approach to reforming the managerial, technical, organizational, and social subsystems of an architectural and construction company. It has been determined that the key frameworks for modernization are unified standards (EN Eurocodes, CPR, ISO 9001, ISO 14001, ISO 45001) and advanced construction concepts (nZEB, ESG, BIM, digital object passports). The scientific apparatus of the article presents a nine-stage algorithm for transitioning to European standards, which includes an audit of the current state, roadmap development, regulatory adaptation, digitalization, personnel transformation, institutional integration, quality certification, ESG implementation, and monitoring mechanisms. Each stage is accompanied by practical recommendations focused on gradual implementation of changes and effective use of internal and external resources. The methodology proposed by the authors is based on an interdisciplinary approach – the integration of architectural theory, ecological economics, digital engineering, risk management, and organizational psychology. Special attention is given to eight key areas of improvement. In the field of regulatory compliance, the focus is on the implementation of EN Eurocodes and CPR, which ensures access to European tenders and increases the investment attractiveness of the company. In the area of energy efficiency, the advantages of implementing certified solutions (BREEAM, LEED, nZEB concepts) are substantiated, as they reduce operational costs, increase market value of assets, and meet the environmental criteria for financing. Digital transformation is addressed through the integration of BIM, ERP/CRM, digital passports, and IoT systems, which enhance the accuracy, transparency, and interconnectivity of project and operational departments. Risk and performance management is presented as the implementation of financial modelling tools (NPV, IRR, CBA, sensitivity analysis), allowing for the optimization of managerial decision-making processes and increased project attractiveness for investors. Systemic personnel transformation, described as a separate improvement line, includes staff certification, introduction of an internal culture of continuous learning, and participation in international educational programs. Institutional integration is outlined through the establishment of partnerships with municipalities, academic institutions, civil society organizations, and European platforms (Horizon Europe, EU BIM Task Group, etc.). The area of quality management and certification emphasizes the gradual implementation of ISO 9001, 14001, and 45001, which enhance the organizational maturity of the company and expand opportunities for participation in international projects. The final area is ESG orientation: implementation of sustainable development principles, inclusivity, transparent reporting, and social responsibility. The methodological basis of the study is formed using system-structural analysis, bibliometric review of publications (Web of Science, Scopus), benchmarking, SWOT analysis, empirical modelling, and logical-inductive synthesis. This made it possible to combine scientific theoretical conclusions with practical tools for their implementation in the management practice of an architectural and construction company.